A implementação do você em cartas pessoais norte-riograndenses do século XX - Moura, Kássia Kamilla de (2013)
Considering the theoretical and methodological presuppositions of Variationist Sociolinguistics (cf. WEINREICH; LABOV; HERZOG, 2006; LABOV, [1972] 2008), in this dissertation, we describe and analyze the process of variation/change involving the personal pronouns tu and você, and its extension in the pronominal paradigm in Brazilian Portuguese (BP), in three sets of personal letters written by people from Rio Grande do Norte (RN) along the 20th century. The discursive universe of those letters is news from the cities in which the informers lived and the themes from their everyday life (trade, jobs, trips, family and politics). Part of the analyzed letters integrate the written by hand minimum corpus of the Projeto de História do Português Brasileiro no Rio Grande do Norte (PHPB-RN). We are based on previous studies about the pronominal system in BP Menon (1995), Faraco (1996), Lopes e Machado (2005), Rumeu (2008), Lopes (2009), Lopes, Rumeu e Marcotulio (2011), Lopes e Marcotulio (2011) e Martins e Moura (2012) , which register the form você replaces tu from the end of the first half of 20th century and attest the following situation: while (a) the imperative verbal forms, (b) the explicit subjects and (c) prepositional complement pronouns are favorable contexts for você, the (d) non imperative verbal forms (with null subject), (e) the non prepositional complement pronoun and (f) the possessive pronoun are contexts of resistance of tu. The results got in this dissertation confirm, partially, the statements defended by the previous studies regarding the favorable contexts for the implementation of você in BP: (i) there are, in the letters from the first two decades of 20th century (1916 to 1925), high frequency of the usage of the form você (98%); (ii) in the personal letters of RN especially in the love letters, in which there are higher recurrence of intimate subjects the discursive universe proved to be itself very relevant in the determination/conditions of the forms of tu; (iii) the unique feminine informer of our sample uses, almost categorically, the forms of tu in letters of the period from 1946 to 1972; (iv) the letters corresponding to the period from 1992 to 1994 present a significant usage of the forms associated to the innovating você, letting appear the change is already implemented in the system of BP and there are, in that set of letters, strong evidences that make us state the pronominal forms of non prepositional complement (accusative/ dative) related to tu are also implemented in a system with an almost categorical usage of você